Cultivars and Fruit Part as Differentiating Factors of Physicochemical Characteristics of Mango Starches - Lossolli, Nathalia Aparecida Barbosa [UNESP]; Leonel, Magali [UNESP]; Leonel, Sarita [UNESP]; Izidoro, Maiqui [UNESP]; de Paula, Gustavo Veiga [UNESP]; dos Santos, Thais Paes Rodrigues [UNESP]; de Oliveira, Luciana Alves (MDPI, 2023)
Fruit production has increased, which has led to an increase in fruit wastage, opening up new opportunities for the use of non-standard fruits as starch sources. Herein, the physicochemical properties of mango starches isolated from the pulp and kernel of four cultivars were investigated. The pulp starches showed higher purity with total starch ranging from 97.84 to 98.09% (dry basis). The kernel starches had a higher percentage of other components (ash, fiber, lipids, protein, sugars). The main mineral in the starches was potassium (0.37 to 1.32 g/kg). Pulp starches were circular and smaller (15–79 to 16.70 µm) and kernel starches were oval and larger (19.75 to 25.33 µm). Differential scanning calorimetry and rapid viscosity studies showed that the kernel starches had higher gelatinization properties. The mango starches were A-type with varying crystallinity levels (28.37–32.35%). PCA analysis showed the greater impact of gelatinization properties on the grouping of cultivars. These findings would be useful for adding commercial value to mango agricultural and industrial waste and for industries in terms of using the starch as an ingredient in food products and other industrial applications.
Keywords: chemical composition; fruit starch; kernel; Mangifera indicaL; mesocarp; structure; technological properties